Application of the flux bending effect inan active flux-guide for low-noise planar vector TMR magnetic sensors - Luong Van Su; Nguyen Anh Tuan; Nguyen Anh Tue; Nguyen Tuyet Nga; Hoang Quoc Khanh; Nguyen Ngoc Lan; Nguyen Tuan Anh (Vietnam Journal of Science and Technology, 2018)
A concept of a planar vector magnetic sensor comprising in-plane tunnel magnetoresistive (TMR) sensors and an active flux-guide (AFG) was introduced in this work. The AFG redirected the magnetic flux at high-frequency benefiting the vertical detection capability and lessening the noise of the TMR at low-frequency measurement. The vertical sensitivity of 19.5 V/T was almost the similar the in-plane sensitivity of 19.2 V/T. In addition, the 1-Hz field noise was suppressed from 6 nT/sqrt-Hz down to 0.4 nT/sqrt-Hz. The flux bending effect of the AFG was also verified by the angular measurements with the deflected angle was found to be about 50º. It revealed that the vertical field component was certainly detected by the in-plane sensor and the proposed method was a feasible technique for the development of the low-noise planar three-dimensional magnetic sensor